Persepsi Guru tentang Pelaksanaan Supervisi Akademik oleh Pengawas Sekolah di Sekolah Dasar Negeri Kecamatan 2X11 Enam Lingkung - Novrita Alfitri; Rifma Rifma; Ahmad Sabandi; Anisah Anisah (Journal of Educational Administration and Leadership, 2022)
The purpose of this study is to find out teachers’ perceptions about planning, implementation, evaluation, and follow-up of academic supervision carried out by school supervisors. This type of research is a quantitative descriptive study, and those who collect data using a questionnaire with a likert scale. This study shows the implementation of academic supervision by supervisors according to teacher perceptions, which can be broken down based on indicators, namely: 1) academic supervision planning has a score of 3,57 in sufficient criteria, 2) the implementation of academic supervision has a score of 3,64 in good criteria, 3) the evaluation of academic supervision has a score of 3,55 in sufficient criteria, 4) follow-up academic supervision has a score of 3,60 in good criteria. Overall the implementation of academic supervision by school supervisors at SDN Subdistrict 2X11 Enam Lingkung, according to the perception of the teacher has a value of 3,59 in sufficient criteria.